Salud mental en víctimas de la violencia armada en Bojayá (Chocó, Colombia) (2005)
ABSTRACT: Purpose: To describe the mental health status of victims of an armed combat in the state of Chocó (Colombia). Method: A description of the mental disorders associated with a traumatic experience lived on May 2nd 2002 (Bojayá township- Colombia), as a consequence of an armed confrontation, resulting in 119 persons dead and 98 injured. Analytic level methodology, with case control design, was used. A non random sample of 40 civilian adults, mean age 35 years, was studied. Of these, 19 persons returned to their place of origin and 21 persons remained in Quibdó (state capital) were evaluated. The case group consisted of a total of 15 persons with Posttraumatic Stress Disorder (PTSD) and the control group included 25 persons without PTSD diagnosis. The instrument used for evaluation was the structured interview pro– tocol M.I.N.I applied one year after the tragic event. Results: Disorders that showed greater association with PTSD were: Social Phobia (p=0.001, OR 26.29), Actual Panic Disorder (p=0.008, OR 15.33), Occasional Panic Disorder (p=0.019, OR 8.25), and Agoraphobia without Panic History (p=0.024, OR=11.50). The prevalence of was high for the following disorders, without significant differences between groups: Major Depression (MD) (37% cases and 38% controls), Suicide Risk (37% y 62% respectively), Generalised Anxiety Disorder (GAD) (47% and 38% respectively). Conclusions: Victims of armed violence who suffer PTSD are at high risk of presenting other anxiety disorders such as social phobias, GAD, and panic attacks.